(3eNJUQ Jbhje GddSGfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3Efi deG QCjJ cJGH Jbhje GddSGf GdPi Cdag GHf GdLhRi QMeg Gddg cJGHkG fGaYkG LeY ajg cKjQkG eeG jZdW ajg GdYGeI Cfg dGaGFOI ai PcQgG s
(3BNQgG (B:s
(3dG jUHh , dCfg ef GdUHh hgh Gddgh hGdjhe aYdJ eG OGeJ GdTeS WGdYI , aEPG ZQHJ aCeS GdCMOK , dCf Gdjhe GfbVi fLR cJGH Jbheje GddSGf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B218 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GddZIs